Hierarchical TiO2 Photoanodes with Spatial Charge Separation for Efficient Oxygen Evolution Reaction. Issue 6 (5th November 2020) - Dong, Guojun; Cheng, Xiang; Bi, Yingpu
Abstract : Charge separation and transfer are crucial to determine photoelectrochemical (PEC) water splitting performance. Herein, a hierarchical bottom‐up approach for fabricating TiO2 nanorod arrays with an Au nanolayer and Sn3 O4 cocatalysts is demonstrated. The hierarchical Sn3 O4 /TiO2 /Au photoanode exhibits a significantly enhanced photocurrent density of 2.5 mA cm −2 at 1.23 VRHE under AM 1.5G irradiation, which is about 5 times higher than that of pristine TiO2 (0.5 mA cm −2 at 1.23 VRHE ). The significantly enhanced PEC properties are attributed to the spatial charge separation among Au nanolayer and Sn3 O4 cocatalysts. More specifically, the bottom Au nanolayer can accelerate the electron transfer from TiO2 to fluorine doped tin dioxide (FTO) substrate, and the surface Sn3 O4 nanoflakes can effectively capture holes and provide abundant active sites for oxygen‐evolution reaction. These demonstrations may offer a new insight for rational design and construction of highly efficient TiO2 ‐based PEC devices for solar water splitting. Abstract : A novel strategy for enhancing spatial charge separation and accelerating water oxidation reaction is proposed by constructing hierarchical TiO2 nanorod arrays with an Au nanolayer and Sn3 O4 cocatalysts. The as‐prepared Sn3 O4 /TiO2 /Au photoanode exhibits an excellent photocurrent density of 2.5 mA cm −2 at 1.23 V versus reversible hydrogen electrode under one solar irradiation, about 5 times higher than that of pristine TiO2 .